INFLUENCE RELATING TO THE STRATEGIES OF SOCIOCULTURAL ADJUSTMENT OF THE CULTURAL DISTANCE BETWEEN THE RECIPIENT SOCIETY AND EMITTER COUNTRY OF TWO FOREIGN COMMUNITIES IN MONTERREY - de la Colina, Juan Antonio Doncel (European Scientific Journal, ESJ, 2013)
Being part of a larger project of investigation, our principal aim constitutes the realization of an analysis of the dynamics of social interaction and the way that these dynamics are influenced by the most stereotypic perceptions between the foreign residents in Monterrey’s city (Nuevo León, Mexico). In a previous paper (Doncel, in process of dictum) we tried to verify the hypothesis that, in the case of the communities that are made up of these foreigners, a higher degree of intracommunitarian cohesion corresponds to a minor degree of integration with the reception society. Since the results of this work are not as conclusive as would be required for the complete corroboration of the hypothesis, we decided to add as an independent variable for the measurement of the degree of integration to the reception society the cultural distance between this one and the origin society. So, here we set out the perceived cultural distance, the situations of intercultural conflict and the forms of differentiated adjustment of two foreign communities that we consider as exemplary cases: the Japanese and the Spanish society.